Effects of balance training on physical fitness in youth and young athletes: a narrative review - Gebel, A.; Prieske, O.; Behm, D. G.; Granacher, U. (Strength and Conditioning Journal, 2020)
Balance training (BT) is a well-established training type in many sports and is used to improve postural control. There is evidence that performance enhancements after BT can even translate to other physical fitness measures such as muscle strength and jump performance. Accordingly, this narrative review summarizes the effects of BT on balance performance in youth/young athletes and describes how acute and chronic BT-specific adaptations translate to other physical fitness outcomes. In addition, recent findings on sequencing effects of balance and strength training will be reported. Finally, established dose-response relationships with BT in youth will be presented together with a progression sequence.